Redesign of the Temporary Storage Area for Hazardous Waste at PT XYZ - , Nati; Temmy Wikaningrum (Jurnal Serambi Engineering, 2026)
The rapid growth of the manufacturing sector in Indonesia has significantly contributed to the national economy. However, it has also increased the generation of hazardous and toxic waste (B3). The manufacturing industry is one of the major contributors to B3 waste and is therefore required to comply with Government Regulation No. 22 of 2021 and Minister of Environment and Forestry Regulation No. 6 of 2021. PT XYZ, an automotive spare parts manufacturing company located in the Cikarang industrial area, generates B3 waste including contaminated packaging, used oil, coolant, contaminated scrap metal, and anti-rust residue. Preliminary observations indicate that the existing temporary storage facility (TPS) for B3 waste does not fully comply with technical and regulatory requirements. This study aims to redesign the B3 waste temporary storage facility in accordance with applicable regulations and to calculate the required supporting facilities. The methodology includes identifying the types, characteristics, and quantities of waste generated, evaluating existing conditions, and calculating the required number of containers, pallets ventilation openings, lighting units, spill containment capacity, and forklift access lanes. The results indicate a requirement of 97 drums, 13 spill pallets, and a minimum spill containment capacity of 19.206 m3 for a 90-day storage period. The proposed design measures 9.3 m x 9.1 m x 4.5 m and includes adequate ventilation, 9 LED lamps, a 3-meter-wide forklift lane, hazard-based zoning separation, and a compliant drainage system, thereby improving safety and minimizing environmental pollution risks.